Strain rate influence on human cortical bone toughness: A comparative study of four paired anatomical sites. (July 2017) - Gauthier, Rémy; Follet, Hélène; Langer, Max; Meille, Sylvain; Chevalier, Jérôme; Rongiéras, Frédéric; Peyrin, Françoise; Mitton, David
Abstract: Bone fracture is a major health issue worldwide and consequently there have been extensive investigations into the fracture behavior of human cortical bone. However, the fracture properties of human cortical bone under fall-like loading conditions remains poorly documented. Further, most published research has been performed on femoral diaphyseal bone, whereas it is known that the femoral neck and the radius are the most vulnerable sites to fracture. Hence, the aim of this study is to provide information on human cortical bone fracture behavior by comparing different anatomical sites including the radius and the femoral neck acquired from 32 elderly subjects (50 – 98 y.o.). In order to investigate the intrinsic fracture behavior of human cortical bone, toughness experiments were performed at two different strain rates: standard quasi-static conditions, and a higher strain rate representative of a fall from a standing position. The tests were performed on paired femoral neck, femoral, tibial and radius diaphyseal samples. Linear elastic fracture toughness and the non-linear J-integral method were used to take into account both the elastic and non-elastic behavior of cortical bone. Under quasi-static conditions, the radius presents a significantly higher toughness than the other sites. At the higher strain rate, all sites showed a significantly lower toughness. Also, at the high strain rate, there is no significant difference in fracture properties between the four anatomical sites. These results suggest that regardless of the anatomical site (femur, femoral neck, tibia and radius), the bone has the same fracture properties under fall loading conditions. This should be considered in biomechanical models under fall-like loading conditions. Graphical abstract: Highlights: Under quasi-static loading, there are mechanical differences between sites. Cortical bone toughness significantly decreases under fall-like loading conditions. Under fall-like conditions, there is no more mechanical difference between sites.